PENGARUH DAYA TARIK HUMOR DALAM IKLAN DI YOUTUBE TERHADAP BRAND IMAGE BUKA LAPAK - Josua Situmorang; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Advertisement with humor attraction are often become a popular ads. Ads with humor attraction are used for the purpose of attracting the audience, and making the recipient of the message become in a positive mood, so the probability of receiving messages is better and would be greater. This is used by Bukalapak, which is one of the biggest e-commerce companies in Indonesia, where they consistently used the humor attraction in every ads they have been made, it is considered good enough seen by the positive response from audiences and some of the awards that they get in the advertising. Advertisement represents the company as a media of communication, indirectly can create a perception about the company in audiences mind. This perception that will become an image or brand image. Brand image is the result of a consumer's view or judgment of a brand whether it is good or bad. This is become the underlying researcher, which want to know if there is an effect between the humor attraction in the advertisement of Bukalapak "Nego Cincai" edition on youtube to brand image of Bukalapak.The theory that used in this study is theory S-R. The method that used in this study is a quantitative explanation method. Data collection techniques in this study using a questionnaire. The number of sample in this study are 100 respondents, and using random sampling for choosing respondens. To influence the two variables, researcher used a simple linear regression analysis. As for processing the questionnaire test, is used the Statistical Product And Service Solution (SPSS) Windows version 25.Based on a simple linear regression to the research effect of humor attraction in advertation at youtube to brand image of Bukalapak, the regression coefficient values obtained in this study is Y = 8,992 + 0,415 X with a significant level of 0,00 that smaller than α = 0.05. It mean there is an effect of humor attraction in advertation at youtube to brand image of Bukalapak, the effect takes 38,6 %, and it is in low influence category. The remaining 61.4% is effected by other variables that are not included in this research. That percentages number show that advertisement with humor attraction can effect the brand image, but its not the only way for companies to create positive image for their brand or product, there is other factors that need to be considered to create brand image. And with these results, so in this study found that H0 rejected and Ha accepted. Keywords: Advertising, Attraction in advertisement, Humor attraction, Brand image